2006
DOI: 10.1021/ja067612p
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Oxidative Addition of the Aryl Carbon−Oxygen Bond to a Ruthenium Complex and Consideration of the Relative Reactivity between Aryl Carbon−Oxygen and Aryl Carbon−Hydrogen Bonds

Abstract: When RuH2(CO)(PPh3)3 was reacted with 2,2-dimethyl-1-(2-p-tolylphenyl)propan-1-one (2), the ruthenium-aryloxy complex 3 was obtained in 76% yield. The structure of this complex was determined from 1H and 31P NMR and X-ray data. Complex 3 showed the catalytic activity for the coupling of 2 with the phenylboronate 4. The 1H and 31P NMR studies of the reaction of Ru(CO)(PPh3)3 with o-aryloxy pivalophenone revealed that the C-H bond cleavage is a kinetically favorable process but the C-O bond cleavage is a thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(80 citation statements)
references
References 17 publications
1
79
0
Order By: Relevance
“…32 Subsequently, Kakiuchi and Chatani shed light into the mechanism highlighted in Scheme 16 by the successful isolation of the oxidative addition complex of an aryl C-O bond using lowvalent ruthenium complexes and ketones as directing groups at the ortho position (Scheme 17, bottom right). 33 Interestingly, no Ru(II) metallacycle derived from the functionalization of ortho C-H bonds could be detected in the crude reaction mixtures. Careful monitoring of a stoichiometric reaction revealed a rather surprising finding regarding the relative reactivity of proximal C-H and C-O bonds.…”
Section: Suzuki-miyaura Type Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Subsequently, Kakiuchi and Chatani shed light into the mechanism highlighted in Scheme 16 by the successful isolation of the oxidative addition complex of an aryl C-O bond using lowvalent ruthenium complexes and ketones as directing groups at the ortho position (Scheme 17, bottom right). 33 Interestingly, no Ru(II) metallacycle derived from the functionalization of ortho C-H bonds could be detected in the crude reaction mixtures. Careful monitoring of a stoichiometric reaction revealed a rather surprising finding regarding the relative reactivity of proximal C-H and C-O bonds.…”
Section: Suzuki-miyaura Type Reactionsmentioning
confidence: 99%
“…31,33 In 2008, Chatani and Tobisu overcame such limitation by designing an elegant Ni-catalyzed SuzukiMiyaura coupling reaction of aryl methyl ethers with organoboron reagents (Scheme 18). 34 Practicality and novelty aside, such a method offered new vistas for the utilization of aryl methyl ethers in cross-coupling reactions, a field that has largely been dominated by the employment of highly reactive and air-sensitive Grignard reagents.…”
Section: Suzuki-miyaura Type Reactionsmentioning
confidence: 99%
“…Although direct arylation of ArÀH or even ArÀOR substrates has received a great deal of attention in recent years, [144] the arylation of Ar À OH has not. [145] In 2008, Kang and co-workers reported that the bromophosphonium salt PyBroP can be employed as an in situ activating agent to allow the direct arylation of tautomerizable heterocycles by Suzuki-Miyaura coupling.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…However, this breakthrough was overlooked for decades, until quite recently. After the development of improved conditions, ArOR can now be used as a coupling partner in several types of transition metal (TM)-catalyzed cross-couplings and related transformations, such as Suzuki-Miyaura-type (B), [24][25][26][27][28][29][30][31] Negishi-type (Zn or Al), [32][33][34][35][36] Murahashi-type (Li), [37][38][39][40] and other reactions. [41][42][43][44][45][46][47][48][49][50] As a continuation of our work in this area, we reported in 2012 the first ethereal Negishi-type coupling of aryl alkyl ether 36) (Chart 1(1)) and in 2016 we reported a systematic examination of ethereal Murahashi-type reaction 37) (Chart 1(2)).…”
mentioning
confidence: 99%